EFEKTIVITAS TEKNIK CLUSTERING (PENGELOMPOKAN) DALAM PEMBELAJARAN MENULIS TEKS LAPORAN HASIL OBSERVASI - Yulia, - (2014)
The purposes of this study are to obtain the representation the student's ability to write the text of observation reports before and after used clustering (grouping) Technique, as well as to examine the significant differences between the student's ability to write the text of observation reports with the student's ability to write the text of observation report used discussion technique. The populations in this study were tenth grade students of SMA Negeri 1 Rancaekek academic year of 2013/2014. The samples in this study were two classes that determined in randomly without regarding the strata of the populations. The class that is used in this study is X IPS 4 as experiment class and X IPS 2 as control class. This study used an experimental research design with group of pretest-posttest research. Based on the acquired data, the average pretest score of experimental class is 68,53 and the average posttest score is 80,17, while the average posttest score of control class is 59,00 and the average posttest score is 63,92. Based on the calculation of hypothesis testing that calculated by t-test the result is 2,005 ≤ 3,66 or Ttable ≤ Tcount ≥ Ttable. This means that H0 is rejected H1 is accepted. This study proved that clustering technique (grouping) is effectively implemented in learning writing especially in learning writing the text of observation reports. Therefore, the writer hope that the teachers use clustering techniques as an alternative technique fatherly teaching of writing to improve the ability to write the text of observation reports. Keyword: Writing, The text of Observation Reports, Clustering Techniques. Penelitian ini bertujuan untuk memperoleh gambaran kemampuan menulis teks laporan hasil observasi siswa sebelum dan sesudah menggunakan teknik clustering (pengelompokan), serta mengkaji ada atau tidaknya perbedaan yang signifikan antara kemampuan menulis teks laporan hasil observasi siswa dengan menggunakan teknik clustering (pengelompokan) dengan kemampuan menulis teks laporan hasil observasi siswa dengan menggunakan teknik diskusi. Populasi dalam penelitian ini adalah seluruh siswa kelas X SMA Negeri 1 Rancaekek Tahun ajaran 2013/2014. Sampel dalam penelitian ini adalah dua kelas yang ditentukan secara acak tanpa memerhatikan strata dalam populasi tersebut. Kelas yang digunakan adalah kelas X IPS 4 Sebagai kelas eksperimen dan X IPS 2 sebagai kelas kontrol. Penelitian ini menggunakan metode penelitian eksperimen dengan desain penelitian group pretes-postes. Berdasarkan data yang diperoleh, nilai rata-rata pretes kelas eksperimen adalah 68,53 dan postes 80,17, sedangkan kelas kontrol nilai rata-rata postes adalah 59,00 dan postes 63,92 . Berdasrkan perhitungan uji hipotesis yang dilakukan dengan penghitungan uji-t, hasilnya adalah 2,005 ≤ 3,66 atau ttabel ≤ thitung ≥ ttabel. hal ini berarti H0 ditolak dan H1 diterima. Penelitian ini membuktikan bahwa teknik clustering (pengelompokan) efektif digunakan dalam pembelajaran menulis khususnya dalam pembelajaran menulis teks laporan hasil observasi. Oleh karena itu, penulis berharap para guru menggunakan teknik clustering (pengelompokan) sebagai teknik alternatif unutk pembelajaran menulis untuk meningkatkan kemampuan menulis teks laporan hasil observasi. Kata Kunci: Menulis, Teks Laporan Hasil Observasi, Teknik Clustering.